The Effectiveness of Positive Psychology Therapy on Cognitive Fusion and Emotion Regulation in Military Medical Nurses of the Islamic Republic of Iran with Depressive Symptoms - Bakhtiary, Saber; AghaYosefi , Alireza; Davoodi , Abdolvahid (Mental Health and Lifestyle Journal, 2025)
This study aimed to examine the effectiveness of positive psychology therapy in improving cognitive fusion and emotion regulation among military medical nurses in the Islamic Republic of Iran who exhibited depressive symptoms. The research employed a semi-experimental pre-test–post-test design with a control group. Thirty nurses were selected from seven military hospitals in Tehran using purposive sampling based on elevated scores on a depression questionnaire, followed by clinical interviews to confirm depressive symptoms. Participants were randomly assigned to an experimental group (n = 15) receiving ten sessions of group-based positive psychology therapy, or a control group (n = 15) receiving no intervention. The intervention included structured practices such as mindfulness, gratitude journaling, savoring, and strength identification. Data were collected using the Cognitive Fusion Questionnaire (CFQ) and the Emotion Regulation Questionnaire (ERQ), and analyzed using multivariate analysis of covariance (MANCOVA), following checks for statistical assumptions. The inferential analysis revealed statistically significant improvements in both outcome variables for the experimental group. ANCOVA results for cognitive fusion showed a significant group effect, F(2, x) = 14.09, p < 0.001, with a large effect size (η² = 0.33). Similarly, results for emotion regulation were also significant, F(2, x) = 13.90, p < 0.001, indicating a strong impact of the intervention on enhancing adaptive emotional regulation strategies. All statistical assumptions were met, and the intervention demonstrated high power in detecting effects. The findings indicate that positive psychology therapy is an effective intervention for reducing cognitive fusion and enhancing emotion regulation among nurses experiencing depressive symptoms in high-stress military healthcare settings. These results support the broader application of strengths-based psychological approaches to promote resilience and emotional well-being in clinical occupational environments.